Exploring growth linkages and market opportunities for agriculture in Southern Africa - Nin-Pratt, Alejandro; Diao, Xinshen (International Food Policy Research Institute, 2006)
Considering the heterogeneity of the countries of southern Africa and the presence of South Africa and other middle-income countries in the region, southern Africa has a unique opportunity to exploit agricultural potential and regional trade opportunities through regional dynamics and integration. We analyze the implications of such opportunities for the growth of the low-income countries, using a regional general equilibrium model that captures growth linkages. We find that growth in the middle-income southern African countries, such as South Africa, benefits the region’s low-income countries through increased demand for their agricultural exports. Agricultural productivity growth, however, is necessary for low-income countries to take advantage of South Africa’s growth. Productivity growth in the low-income countries’ grain and livestock sectors generates more growth in GDP and food consumption than growth in nontraditional export crops. Unlike other regions where growth in grain production is likely to be constrained by domestic demand, expanding middle-income economies in southern Africa provide additional demand for grains and livestock, slowing the decline in grain prices in the region.